Heart failure and atrial fibrillation: updates and perspectives - V. N. Larina; I. K. Skiba; A. S. Skiba; V. G. Larin; E. A. Vartanyan (Российский кардиологический журнал, 2022)
The article discusses modern approaches and features of management, as well as predicting the risk of complications in patients with cardiac arrhythmias, in particular, atrial fibrillation, and the potential of using conservative and interventional treatment methods for heart failure (HF), taking into account updates and achievements in clinical practice. Epidemiological data, algorithms for managing patients with HF and atrial fibrillation, prevention of thromboembolic events, results of studies comparing the effectiveness of different strategies for atrial fibrillation treatment, catheter ablation compared with drug therapy in patients with HF are presented.